2009
DOI: 10.1167/iovs.09-3462
|View full text |Cite
|
Sign up to set email alerts
|

The Drusenlike Phenotype in AgingCcl2-Knockout Mice Is Caused by an Accelerated Accumulation of Swollen Autofluorescent Subretinal Macrophages

Abstract: These findings suggest that the lack of Ccl2 leads to a monocyte/macrophage-trafficking defect during aging and to an impaired recruitment of these cells to sites of laser injury. Other, previously described features of Ccl2(-/-) mice that are similar to AMD may be the result of aging alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
190
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(217 citation statements)
references
References 28 publications
21
190
1
5
Order By: Relevance
“…The authors detected macrophages and pigment in subretinal cells and concluded that they were the source of sub-RPE deposits. 56 We investigated choroidal vasculature using light and electron microscopy as well as FITC-dextran angiography because it is reported that reduction of choroidal vascularization may contribute to dry AMD. 2e4 Although FITC-dextran angiography is not a commonly used method to quantify choriocapillary density in naive animals, it is a well-accepted method to investigate choroidal neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…The authors detected macrophages and pigment in subretinal cells and concluded that they were the source of sub-RPE deposits. 56 We investigated choroidal vasculature using light and electron microscopy as well as FITC-dextran angiography because it is reported that reduction of choroidal vascularization may contribute to dry AMD. 2e4 Although FITC-dextran angiography is not a commonly used method to quantify choriocapillary density in naive animals, it is a well-accepted method to investigate choroidal neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Vacuolation (2/7 eyes) ( Figure 5f) and formation of multiple layers of hypopigmented retinal pigment cells (2/7 eyes) ( Figure 5g) were observed in the Rbp4 − / − retinal pigment epithelium. Large, irregular, macrophage-like cells (3/7 eyes) 24 appeared between the INL and retinal pigment epithelium in the regions where severe photoreceptor loss developed (2/7 eyes) (Figures 5g and h). One of the Rbp4 − / − mice had retinal structure collapse including disappearances of both retinal and choroidal layers in the peripheral retina (Figure 5i).…”
Section: Histological Comparison Of the Retinas Of Rbp4 +/+ Andmentioning
confidence: 99%
“…First was the supposition that the ∼25-μm diameter AF cells observed in the OS layer shown in Fig. 1A could represent infiltrating microglia/macrophages (40,41). Translocation of microglia/macrophages into the subretinal space is one of the features of retinal inflammation found in degenerating retinas (42,43).…”
Section: Tpm Noninvasively Images Autofluorescence (Af) Signals Frommentioning
confidence: 99%
“…Translocation of microglia/macrophages into the subretinal space is one of the features of retinal inflammation found in degenerating retinas (42,43). A second concern was that even though retinal infiltrating cells had been imaged by SLO as AF granules in Abca4 −/− Rdh8 −/− mice after light illumination (41,42), neither their fluorescence spectra nor their z location within the retina were known. Here we found increased numbers of SLO AF granules at day 3 that peaked at day 7 after light exposure [ Fig.…”
Section: Tpm Noninvasively Images Autofluorescence (Af) Signals Frommentioning
confidence: 99%